ENHANCING READING FLUENCY AND COMPREHENSION IN ORAL READING THROUGH READING THEATRE - Nais Saraswati; Mbarep Wicaksono (Universitas Teknokrat Indonesia, 2021)
Comprehension is the key of success reading. Researchers have shown that reading comprehension is improved when fluency increased. In order to construct the meaning of the text, instructional strategy which helps English language learners decode word until they fluently read and understand must be applied. This paper focuses on discussing the effects of using Readers Theatre as strategy to enhance English language learners fluency and comprehension in oral reading. It also provides the overview of the use of repeated reading. Readers Theater in particular, the role of fluency and comprehension in reading and the correlation about how fluency influences reading comprehension.